ACEH CATTLE FOLLICLE DYNAMIC UNDER ENVIRONMENTAL HEAT STRESS - Armansyah, Teuku; Siregar, Tongku Nizwan; Aliza, Dwinna; Melia, Juli; Meutia, Nellita; Panjaitan, Budianto; Hafizuddin, Hafizuddin; Adam, Mulyadi; Abrar, Mahdi (Universitas Syiah Kuala, 2017)
The objective of this research is to know Aceh cattle follicle dynamic under environmental heat stress condition. This research was conducted on December 2012 until August 2013. Animals used in this research were 20 Aceh cattle aged 5-8 years old, weighing of 150-250 kg, and had at least 2 regular cycles. All cattle used were clinically in good body condition score. The cattle were divided into two groups of 10, used in two different period of times (December-January and July-August) to examine the effect of environmental heat to their follicle dynamic. Each group is separated into two different keeping management; one group was kept in pens while the others in the pasture, 5 cattle in each management group. Research timing was based on information acquired from Indrapuri Agency for Meteorology, Climatology, and Geophysics (BMKG) which predicted that extreme weather would last from July to August while December to January would be relatively normal in Aceh region. All cattles estrous cycle were synchronized by 5 mg/mL of PGF2 intramuscularly (Lutalyse, Pharmacia Upjohn Company, Pfizer Inc.). Ultrasonography examination was performed to monitor ovary follicles growth and dynamic during one cycle. Days during ovulation marked by standing heat was regarded as Day 0 of estrous cycle. Follicular dynamic examination during estrous cycle on December-January and also on July-August, both penned or pastured cattle showed the follicle waves that was 3 follicle growth waves. The size of follicle growth on first wave (1st DF) on cattle kept in pen on July-August and December-January were relatively similar. The size of follicle growth on first wave for cattle kept in pasture on July-August and December-January were relatively similar. To conclude, Aceh cattles follicle dynamic is not change during environment heat stress condition and is not affected by different cattle-keeping management.